2022
DOI: 10.3389/fmicb.2022.905668
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Gut Microbiota of Three Sympatric Terrestrial Wild Bird Species Overwintering in Farmland Habitats

Abstract: The gut microbiota of wild birds are affected by complex factors, and cross-species transmission may pose challenges for the host to maintain stable gut symbionts. Farmland habitats are environments strongly manipulated by humans, and the environmental characteristics within a large area are highly consistent. These features provide the ideal natural conditions for conducting cross-species comparative studies on gut microbiota among wild birds. This study aimed to investigate and compare the gut microbiota of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
3
4
0
Order By: Relevance
“…Twenty fecal samples were used in our study, identifying 10 bacterial phyla and 9 fungal phyla. The bacterial phyla were primarily made up of Firmicutes and Proteobacteria, and this result was consistent with earlier studies on other birds, including the bar-headed goose ( Dong et al., 2021 ), Whooper Swan ( Wang et al., 2021 ), Great Bustard, Common Coot , and Common Crane ( Lu et al., 2022 ). Animals have a large distribution of Firmicutes, essential to hosts in sustaining energy metabolism ( Kaoutari et al., 2013 ) and as a gauge of fecal health ( Ley et al., 2006 ).…”
Section: Discussionsupporting
confidence: 91%
“…Twenty fecal samples were used in our study, identifying 10 bacterial phyla and 9 fungal phyla. The bacterial phyla were primarily made up of Firmicutes and Proteobacteria, and this result was consistent with earlier studies on other birds, including the bar-headed goose ( Dong et al., 2021 ), Whooper Swan ( Wang et al., 2021 ), Great Bustard, Common Coot , and Common Crane ( Lu et al., 2022 ). Animals have a large distribution of Firmicutes, essential to hosts in sustaining energy metabolism ( Kaoutari et al., 2013 ) and as a gauge of fecal health ( Ley et al., 2006 ).…”
Section: Discussionsupporting
confidence: 91%
“… 2018 , Hird et al 2018 , Maraci et al 2021 , Bartlow et al 2022 ). In many cases, differences in the gut microbiota were still apparent despite sympatric occurrence and similar habitat types used by different species (Yang et al 2016 , Cho and Lee 2020 , Lu et al 2022 but see Grond et al 2019 ), which is consistent with our results. It has also been suggested that diet and feeding preferences are among the most important drivers of interspecific variation in the composition of gut microbiota, not only in shorebirds, but also in other avian lineages (Grond et al 2018 , Matheen et al 2022 , Sun et al 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…The investigation of the gut microbiota in the Galapagos penguin Spheniscus mendiculus revealed the presence of five putative pathogenic taxa, including one taxon ( Clostridium perfringens ) with extremely high prevalence (95% samples) (Rohrer et al 2023 ). The analysis of the gut microbiota in three nonpasserine bird species (great bustard, common crane, and common coot Fulica atra ) during the winter period revealed the presence of 13 potentially pathogenic genera, but all showed rather low (< 4%) relative abundance (Lu et al 2022 ). In our study we detected nearly 60 species of putative pathogenic bacteria in faecal samples from shorebirds migrating though Poland and eight of them were found in all study hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the mechanisms of coexistence of different species in the same location at a microscopic level helps us better understand the relationship between host and gut microbiota, and also allows us to understand the dietary preferences of different species under similar dietary conditions ( Fu et al, 2021 ). Previous studies have shown that three species that depend on farmland in the same region, Otis tarda dybowskii , Grus grus , and Fulica atra , maintain distinct gut microbiota structures during the wintering period in the same habitat, despite similar external factors ( Lu et al, 2022 ). Researchers believe that species symbiosis is promoted by the gut microbiota, which is independently driven by each host ( Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that three species that depend on farmland in the same region, Otis tarda dybowskii , Grus grus , and Fulica atra , maintain distinct gut microbiota structures during the wintering period in the same habitat, despite similar external factors ( Lu et al, 2022 ). Researchers believe that species symbiosis is promoted by the gut microbiota, which is independently driven by each host ( Lu et al, 2022 ). In a study on the co-distribution of Great Bustards and Common Cranes, differences in gut microbiota abundance and diversity were found between the two species.…”
Section: Introductionmentioning
confidence: 99%